Determination of Selected Profile and Productivity Characteristics of Soils Formed on Meriç River (Turkey) Terraces - Orhan Yüksel; Hüseyin Ekinci (Turkish Journal of Agriculture: Food Science and Technology)
This study was conducted to determine profile and productivity characteristics of soils formed over the alluvial terraces located at different elevations and distances from Meriç River. Soil profiles were sampled at four different points located vertically at different distances from Meriç River and soil horizons were defined in these profiles. Twenty-eight disturbed soil samples were taken, and physico-chemical analyses were performed on these profile samples. While paddy farming is practices over the fields where profile 1 (P1), profile 3 (P3) and profile 4 (P4) are located, the field where profile 2 (P2) is located has long been used as pasture. Organic matter content of soils was generally “low” and “very low”. The highest organic matter contents were observed in A1 horizon of P2 (3.22%) and Ap horizon of P4 (2.09%). Soil pH values were generally “slightly acidic” and “neutral”. Soils were “calcareous” in P2 and “slightly calcareous” in the other profiles. Salinity was encountered in P2. Electrical conductivity (EC) of A1 horizon of this profile was measured as 6.51 dS m-1. Sodium (Na) content of this horizon was also “very high”. As compared to other profiles, P2 was located at a lower elevation, thus wet through majority of the year. Therefore, P2 was generally wet and had redoximorphic characteristics, high clay content and thus poor drainage conditions. P1 was located at the closest position to the river, thus had higher sand contents than the other profiles. Based on clay content, cation exchange capacity (CEC) was the greatest in P2 and the lowest in P1. Available nutrient contents of the profiles decreased through the depth of the profile. Phosphorus (P), iron (Fe), cupper (Cu), manganese (Mn) and zinc (Zn) contents of upper layers were “sufficient” and “excessive”. On the other hand, potassium (K) content was “sufficient” only in P2 and “low” in the other profiles.